Ice – water – vapour : anthropogenic curating of glaciers as a tool to reconnect human development to the biosphere - Bünter, Evelin Sonja, 1985- (2017)
In this paper, I am drafting the concept of anthropogenic curating, based on my research of three major subjects which are a.) the glacier as a system and matter, b.) the connection between human development and the biosphere and c.) the profession of curating. This paper is divided into three sections structured along the physical conditions of a glacier: ice, water and vapour. In the first section Ice I am giving an objective introduction about the glacier as a system of substantial matter. It is about creating knowledge and building a foundation of understanding, curiosity and captivation. The second section Water is about liquefying the solid matter by adding context in terms of planet Earth, climate and contemporary society with their interconnections as factors of transformation. Emptiness, empty space and silence are fluid thoughts which are discussed within this context. In the third section Vapour I am developing the idea of a possible future form of curating by merging the history of curation as a profession with the subjects of the previous sections Ice and Water. I am visualising anthropogenic curating as a tool to vaporise the solid and liquid matter and therefore enable man to create new futures and cultures. Besides studying a diverse selection of literature, I have placed great emphasis on personal contact, both with people and with nature, throughout the process of my research and writing of this thesis. I kept on visiting Sólheimajökull, Snæfellsjökull and Breiðamerkurjökull several times to feel the subject of my writing deeply within me. I engaged in conversations with professionals of a large variety of fields during the 4th Assembly of the Arctic Circle Conference in Reykjavík as well as consulting extensively with Oddur Sigurðsson, glaciologist at the Icelandic Meteorological Office.